Análise geológica e ambiental dos processos erosivos em Aparecida de Goiânia (GO) - Fernandes, Rodrigo Luiz Gallo (2023)
The conceptions of urban territorial planning encompass the behavior of the soil, the dynamics of fluvial and rainfall waters, and the proposition of measures for environmental preservation and control of negative impacts on urban occupation. Erosion can be considered the main consequence of misuse and misunderstanding of urban occupation, especially in urban centers, causing problems such as drainage siltation, poor water quality, land loss, among others. The main objective of this study was the environmental geological survey of erosive problems in the municipality of Aparecida de Goiânia, in the state of Goiás, Brazil. Specifically, spatial and temporal analysis of erosive processes, inventory mapping of erosive processes, environmental geological characterization of the study area, land use and occupation in the municipality, and analysis of relevant legislation were conducted. Methodologically, literature surveys, photointerpretation, erosion monitoring, and geological material characterization were performed. Existing data from previous studies and photointerpretation were used for the inventory of erosive features. Monitoring of selected erosions was carried out from April 2022 to February 2023, along with photographic records and geological material characterization. Regarding legislation, despite the municipality having strict laws regarding occupation near streams and springs, a lack of enforcement by the public authorities was noticed, allowing occupation in these areas. The study showed that erosive features occur on highly weathered shale materials, which give rise to easily erodible saprolites. The analysis of erosive feature inventories revealed that the behavior of erosive processes varied over the years, in accordance with urbanization evolution. The increase in impermeability and territorial occupation, which occurred without the installation of necessary basic infrastructure, led to a change in the development of erosive processes, observed from the year 2017. It was concluded that the dynamics of erosive processes in the municipality were adequately characterized, especially regarding its relationship with the urbanization process. On the other hand, there was a difficulty in reversing this situation, which may be due to technical and/or political issues, as municipal interventions for erosion control and recovery have proved to be ineffective.